On the Chilean social explosion - Woods, Maxwell, author.
1 online resource.
Keywords: "On the Chilean Social Explosion uses the methods of literary, cultural, and subaltern studies to examine what cultural foundations and practices gave rise to this political uprising. On 18 October 2019, Chile exploded into a series of nationwide protests that placed the socio-political order of neoliberalism, settler colonialism, and patriarchy under structural crisis. In March 2020, however, the quarantining measures taken in response to the COVID-19 pandemic put this grassroots rebellion on pause. The author explores and analyzes these five months which have come to be known as the Chilean social explosion [estallido social]. This book will be of value to researchers of cultural studies, cultural and radical politics, resistance and protest, subaltern studies, and Chilean and Latin American politics. It will also interest a broader audience concerned with social movements, grassroots organizing, and expressions of dissent across the world"--